Game Day Experience through the Lens of Critical Incident Technique - Robin Hardin; Brody Ruihley; Cindy Veraldo (Journal of Applied Sports Management, 2013)
This qualitative study examined the game-day experiences of fans at a college football game using Critical Incident Technique. This technique identifies and examines important occurrences, or incidents, identified by participants based on their own positive or negative experience. A total of 2,450 individuals responded to the optional open-ended question on a survey. Respondents indicated the most positive aspects of the experience as the enjoyment, pride, and tradition associated with attending the games. The facility, atmosphere, and policies and operations were reported as the most negative aspects of the experience. It is important to understand the experience of fans at events because they are one of the primary stakeholders of an organization and one of the primary resources of revenue in the form of ticket sales. Organizations, including collegiate athletic departments, should always be evaluating the consumer experience in order to enhance the experience which can led to higher retention rates of season-ticket holders and also cultivate new season-ticket holders. The delivery of high-quality service is one of the important aspects of any service organizations.
Keywords: Critical Incident Technique; college football; service quality; tickets; fans